Best Formulation Antibacterial Cream From 96% Ethanol Extraction Green Betel (Piper Betle Linn.) - Arif Vanny, Zurroidah; Yulita Fazadini, Safira (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Cream is an emulsion preparation with a water content of at least 60% and used for external application. In the manufacture of cream, active ingredients from green betle leaves one of nature ingredient for making cream. Green betel leaves are reported to contain flavonoids that can inhibit bacterial activity. This study aims to identify the best formula for a cream containing 96% ethanol extract of green betel leaf as the active ingredient by varying the concentration of the active ingredient, applying several stages of the cream preparation process, followed by testing the preparation, namely organoleptic testing, homogeneity testing, pH testing, viscosity testing, spreadability testing, adhesion testing, and cream type testing using the colour and dilution methods. The research result showed that the best formulation was formulation 3 with an extract content of 9, because all tests on formula 3 meet the standard